Teologi Filosofis Islam Soundtrack Serial Anime Dragon Ball - Suyud El Syam, Robingun (Faidatuna, 2024)
Dragon Ball is very popular among different generations in the World. it is not only important in terms of symbolism but also regarding ideology. The purpose of this article is to answer the academic research problem, what content of Islamic philosophical theology is contained in the soundtrack of the Dragon Ball anime series. The study takes a library research setting with a philosophical approach, using Plato's theory of form or the realm of ideas. The results of the study show that the soundtrack for the Dragon Ball anime series contains religious teachings, where the author invites viewers to see the essence of life starting from birth and actually has a purpose in the context of worshiping God. The world is placed as a field to collect the coffers of virtue in order to prepare for the future in the afterlife so that after death the virtue becomes a savior in the wilderness, and the brother lives in heaven in the end. This is an idea or idea that arises from the depths of the heart. Research implications: the importance of understanding the idea of a film soundtrack. The study suggests future in-depth research directions in more specific areas.